6, 7-dimethoxy-1, 2, 3, 4-tetrahydro-isoquinoline-3-carboxylic acid attenuates heptatocellular carcinoma in rats with NMR-based metabolic perturbations. (12th May 2017) - Kumar, Pranesh; Singh, Ashok K; Raj, Vinit; Rai, Amit; Maity, Siddhartha; Rawat, Atul; Kumar, Umesh; Kumar, Dinesh; Prakash, Anand; Guleria, Anupam; Saha, Sudipta
Aim: 6, 7-dimethoxy-1, 2, 3, 4-tetrahydro-isoquinoline-3-carboxylic acid (M1) was synthesized and evaluated for in-vivo antiproliferative action in diethylnitrosamine-induced hepatocarcinogenic rats.Materials & methods: The antiproliferative effect of M1 was assessed by various biochemical parameters, histopathology of liver and HPLC analysis. Proton nuclear magnetic resonance-based serum metabolic study was implemented on rat sera to explore the effects of M1 on hepatocellular carcinoma-induced metabolic alterations.Results: M1 showed protective action on liver and restored the arrangement of liver tissues in normal proportion. HPLC analysis displayed a good plasma drug concentration after its oral administration. Score plots of partial least squares discriminate analysis models exhibited that M1 therapy ameliorated hepatocellular carcinoma-induced metabolic alterations which signified its antiproliferative potential.Conclusion: M1 manifested notable antiproliferative profile, and warrants further investigation for future anticancer therapy. Lay abstract: Our previous study unveiled that an isoquinoline alkaloid (M1) isolated from Mucuna pruriens seeds had potent antiproliferative action on human hepatoma cells in vitro . In the present investigation we synthesized M1 and studied its in vivo antiproliferative effects in liver carcinogenic rats. To observe the effects of M1, various studies were conducted which include biochemical parameters of plasma and serum, histopathology of liver and HPLC analysis of plasma. In addition, 1 H-NMR-based serum metabolic profiling was carried out to identify the effects of M1 on hepatocellular carcinoma-induced metabolic alterations. Our findings showed that compound M1 exemplifies remarkable efficacy against hepatocellular carcinoma.